2014
DOI: 10.1098/rsif.2014.0727
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes and biological responsiveness of an injectable and mouldable monetite bone graft generated by a facile synthetic method

Abstract: Brushite (dicalcium phosphate dihydrate) and monetite (dicalcium phosphate anhydrous) are of considerable interest in bone augmentation owing to their metastable nature in physiological fluids. The anhydrous form of brushite, namely monetite, has a finer microstructure with higher surface area, strength and bioresorbability, which does not transform to the poorly resorbable hydroxyapatite, thus making it a viable alternative for use as a scaffold for engineering of bone tissue. We recently reported the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…[1,2,3,4] Although hydroxyapatite is the calcium phosphate most similar to the mineral component of natural bone, having decent mechanical properties too [5], it is poorly resorbed in the body and different calcium phosphates have been preferred to it, more resorbable and capable of inducing a more optimal bone regeneration process. Among these resorbable calcium phosphates, monetite and brushite are the currently favourite candidates [6,7]. However, although calcium phosphates present ideal bone tissue substitutes from the standpoints of bioactivity and biocompatibility, their state-of-the-art, self-setting formulations suffer from (a) weak mechanical properties, (b) negligible bone growth gene effects without the use of exogenous growth factors, and (c) a lack of intrinsic antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4] Although hydroxyapatite is the calcium phosphate most similar to the mineral component of natural bone, having decent mechanical properties too [5], it is poorly resorbed in the body and different calcium phosphates have been preferred to it, more resorbable and capable of inducing a more optimal bone regeneration process. Among these resorbable calcium phosphates, monetite and brushite are the currently favourite candidates [6,7]. However, although calcium phosphates present ideal bone tissue substitutes from the standpoints of bioactivity and biocompatibility, their state-of-the-art, self-setting formulations suffer from (a) weak mechanical properties, (b) negligible bone growth gene effects without the use of exogenous growth factors, and (c) a lack of intrinsic antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact the treatment of bone defects (i.e. bone deficiency because of trauma, tumour or infections) represents a challenge for orthopaedic surgeons owing to lack of therapeutic approaches that are able to fully restore the lost bone, and brushite cements have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 raised in the last few years special interest because they are resorbed in vivo much faster than bioapatite ones due to their metastable nature in physiological fluids [49][50].…”
Section: A) Modern Bonesmentioning
confidence: 99%
“…It is believed that the brushite is sometimes associated with the formation of HA within the material, which led to decrease the degradation rate as a result of the lower solubility of HA. Monetite is of special interest as it can promote bone formation, owing to its high degradation rate under physiological conditions . Monetite granules implanted in human alveolar defects have formed a higher amount of newly formed bone than HA granules, due to its more resorbability, providing both bone growth space, and ions (calcium and phosphate) for formation of new bone .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the monetite particles were transferred to carbonated apatite when immersed in simulated body fluid (SBF) or cell culture medium (α‐MEM) . In contrast, monetite ceramics in another cell culture media known as Dulbecco's modified Eagle's media (DMEM) with and without cell seeding showed that the crystal structure of monetite was not changed after 3 weeks …”
Section: Introductionmentioning
confidence: 99%